Marketing Responsible Drinking Effectively to Young Adults - Doyle, Colby; Gaudet, Matthew; Lay, Dominic; McLeod, Amber; Schaeffer, Robert (MacEwan University Student eJournal, 2014)
The primary goal of this research is to identify and examine the components of responsible drinking advertisements. We will examine industry and government related advertisements as we try to understand one of our major questions: does the source influence the validity of the message? The next group of major questions that we will be looking to answer is how are the vague quantifiers used in responsible drinking campaigns interpreted by the public?  How many drinks do people consider “too much?” What does “drink responsibly” really mean? The third major question is whether or not an individual’s current consumption patterns of alcohol have any effect on how individuals assess responsible drinking campaigns. Our qualitative research has indicated that social influences can be strongly related with drinking patterns; this will be further examined in our quantitative research. Also, we will be looking into some of the psychology behind industry and government sponsored advertisements as well as gathering and interpreting information from a sample of our target demographic. Our target demographic consists of both male and females between the ages 18-24. Our literature review and qualitative analysis gave us good insight into some of the potential answers to our questions. We will use these potential answers from our previous research to guide us as we attempt to conduct conclusive research based on a sample data of 169 individuals. Our findings will aid us in developing conclusions and recommendations for Alberta Health Services.